Місце Регламенту Верховної Ради України в системі нормативно-правових актів - Свірський, Б.М. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Исследуется правовая природа Регламента Верховной Рады Украины как нового акта в системе нормативно-правовых актов, принимаемых Парламентом Украины. In the article legal nature of Regulation of Verkhovna Rada of Ukraine is probed as a new act in the system of normatively-legal acts, accepted Parliament of Ukraine.